EFIKASI HERBISIDA ISOPROPILAMINA GLIFOSAT 240 g l-1 TERHADAP PERTUMBUHAN GULMA DI PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq) TANAMAN MENGHASILKAN - Wasri (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
Oil palm (Elaeis guineensis Jacq.) Is one of the most widely cultivated plantation crops in Indonesia. The decrease in productivity of oil palm is caused by presence of weeds around the plant that can be controled. One of the most commonly used controls is the use of the isopropylamine glyphosate herbicide. This research aims to determine the dosage of the Isopropylamine glyphosate herbicide which is oil palm yields. Determining changes in weed composition after application of Isopropylamine glyphosate herbicide in oil palm yields. Determining whether phytotoxicity occurs in oil palm yields after application of the Isopropylamine glyphosate herbicide. This research was conducted in oil palm plantations owned by farmers in Jontor Kenangasari Village, Seputih Surabaya District, Central Lampung Regency and the Weed Laboratory of the Faculty of Agriculture, University of Lampung, Gedong Meneng, Bandar Lampung. The research was conducted using a randomized block design (RBD) with 6 treatments and 4 replications, namely various doses of isopropylamine glyphosate (360, 600, 480, and 720 g ha-1), manual weeding, and control. Homogeneity of variance was tested using the Bartlet test, additivity was tested by the Tukey test, and the mean difference was tested by the Least Significant Difference Test (LSD) at the 5% level. The results showed that: (1) The isopropylamine glyphosate herbicide dose of 480-720 g ha-1 is effective in controlling total weeds, grasses weeds, Brachiaria mutica weeds and Mikania micrantha weeds up to 12 MSA and the herbicide dose of 600-720 g ha-1 is effective in controlling wide leaf weeds, and Cyrtococcum acrescens weeds up to 8 MSA, (2) The isopropylamine glyphosate herbicide 360- 720 g ha-1 causes changes in weed composition at 4, 8, and 12 MSA, and (3) Application of the isopropylamine glyphosate herbicide 360 - 720 g ha-1 on plant plates did not cause poisoning to oil palm plants.